The Role of Residential Buyouts in Post-Disaster Housing Recovery Support: A Comparison of Recent Cases from Japan and the United States - Maly, Elizabeth; Kondo, Tamiyo; Banda, Michiko; Iuchi, Kanako (International Planning History Society Proceedings, 2019)
After recent disasters in Japan and the United States, government acquisition of residential land has played a larger and increasing role within and in relation to housing recovery support programs. With different historical, legal, and governance contexts, residential buyouts are shaped by the respective policies of each country. Framed by earlier precedents, this paper explains the development and implementation of residential buyout programs used after recent disasters: the 2011 Great East Japan Earthquake and tsunami in Japan and 2012 Superstorm Sandy in New York City and New York State in the United States. Through a comparison of roles of buyout in relationship to other aspects of postdisaster housing reconstruction and recovery support, some similarities are identified in the challenges of implementation, as well as uniquely different issues faced by the affected communities and households in each case.